Anti-inflammatory composition containing magnesium hyaluronate and application thereof
By improving the preparation method of magnesium hyaluronate and combining with the combination of red mycolytic alcohol, a nanoemulsion with high anti-inflammatory activity was prepared, which solved the problems of multiple replacements and high consumption in the existing processes, and achieved a more efficient and environmentally friendly production process and product performance.
Patent Information
- Application Number
- CN202510109521.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-18
AI Technical Summary
The existing preparation process for magnesium hyaluronate has multiple replacement reactions, consumes a large amount of ethanol, takes a long time and has a large amount of sodium ions remaining in the finished product, which affects its application efficiency.
A sodium hyaluronate aqueous solution and a strong acid cation exchange resin were mixed and stirred, and an insoluble magnesium-containing compound was added after filtration. Magnesium hyaluronate was obtained by freeze-drying, and a nanoemulsion was prepared in combination with red-bromycin alcohol to improve anti-inflammatory activity.
The preparation process is simplified, the use of organic solvents is avoided, the sensitization and production costs are reduced, the anti-inflammatory activities of magnesium hyaluronate and red mycolytic alcohol are enhanced, and their application value in cosmetics is enhanced.
Smart Images

Figure CN119837783A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anti-inflammatory composition containing magnesium hyaluronate and application thereof, belonging to the technical field of cosmetics. Background Art
[0002] Hyaluronic acid (HA) is a high molecular weight acidic mucopolysaccharide with the following structural formula: it is composed of alternating disaccharide units of β-D-glucuronic acid and β-N-acetylglucosamine.
[0003]
[0004] HA is widely distributed in the human body and exists in multiple parts such as dermal connective tissue, synovial fluid, vitreous body, and dental pulp matrix. It is an important type of physiologically active substance. The content of magnesium ions in the human body is second only to sodium, potassium, and calcium, ranking fourth. It is the main cation in the human body and plays an indispensable role in metabolic homeostasis. Studies have shown that there is a link between magnesium deficiency and many diseases, including osteoporosis, metabolic syndrome, stroke, cognitive impairment, hypertension, and type 2 diabetes. As one of the important metal elements in the skin, magnesium ion deficiency can also lead to a series of inflammatory skin diseases, such as dermatitis and psoriasis. Magnesium ions applied externally to the skin can penetrate through the hair follicles and be distributed in the stratum corneum. From an efficacy perspective, magnesium ions can promote the repair of the skin barrier and effectively reduce UVB-induced skin oxidative stress and photoaging.
[0005] At present, the preparation process for magnesium hyaluronate includes: the patent document CN 107840897 A "A hyaluronic acid magnesium salt for treating osteoarthritis and its preparation method and application" reports that sodium hyaluronate is added to a high concentration ethanol solution of magnesium acetate, reacted at about 40 ° C, and a precipitate is obtained by standing centrifugal filtration, and the precipitate is repeated for many times to obtain magnesium hyaluronate. In this preparation process, replacement reaction is required many times, a large amount of ethanol is consumed, it takes a long time, the replacement efficiency is low, and there are still more sodium ions remaining in the finished product. There is also a document "Synthesis and Biological Activity of Several New Hyaluronic Acid Metal Complexes" mentioned that sodium hyaluronate is dissolved in water and then added to a magnesium acetate solution and stirred continuously, and the alcohol precipitation is washed and dried to obtain magnesium hyaluronate. This method dissolves sodium hyaluronate in water and replaces it with magnesium salt, which can only be replaced once, and more sodium ions remain in the finished product. At the same time, the concentration of sodium hyaluronate solution should not be too high. The excessive viscosity of the solution is not conducive to the occurrence of replacement reaction, so the alcohol precipitation process of this method consumes a lot of ethanol.
[0006] Bisabolol, also known as sweet bisabolol and fenfeng root alcohol, is one of the most common sesquiterpene compounds in nature. Its structural formula is as follows:
[0007] Bisabolol can be used in skin care products as an active ingredient for sensitive skin care. It not only has anti-inflammatory properties, but has also been shown to have antibacterial activity, anti-irritation effects, skin protection effects, and repair effects. It can be directly used in wash-off products. Natural bisabolol is a light yellow viscous oil with a slight characteristic odor. It is easily soluble in lower alcohols such as ethanol and isopropanol, and is also soluble in fatty alcohols and glycerides, but is almost insoluble in glycerin and water, which to a certain extent limits its application.
[0008] The present invention combines magnesium hyaluronate with bisabolol to prepare a nanoemulsion, thereby improving the anti-inflammatory activity of magnesium hyaluronate and bisabolol, and can be used in cosmetics such as sensitive skin repair. Summary of the invention
[0009] In view of the deficiencies in the prior art, the present invention provides an anti-inflammatory composition containing magnesium hyaluronate and application thereof. The composition comprises magnesium hyaluronate and bisabolol and has a synergistic anti-inflammatory effect.
[0010] The technical solution of the present invention is as follows: An anti-inflammatory composition comprises the following components: magnesium hyaluronate and bisabolol.
[0011] Preferably according to the present invention, the components of the anti-inflammatory composition are as follows, in parts by mass: 10 to 15 parts of magnesium hyaluronate and 10 to 12 parts of bisabolol.
[0012] Preferably, according to the present invention, the preparation method of magnesium hyaluronate is as follows: a sodium hyaluronate aqueous solution is mixed and stirred with a strongly acidic cation exchange resin, and after the stirring is completed, the filtrate is filtered and collected, an insoluble magnesium-containing compound is added to the filtrate, and after the reaction is completed, the unreacted insoluble magnesium-containing compound is filtered out, and the filtrate is freeze-dried to obtain magnesium hyaluronate.
[0013] Further preferably, the molecular weight of the sodium hyaluronate is 3 kDa~3000 kDa, and the concentration of the sodium hyaluronate aqueous solution is 0.1~10%, by mass percent.
[0014] Further preferably, the strong acid cation exchange resin is a strong acid styrene cation exchange resin with a cross-linking degree of 5 to 10%.
[0015] More preferably, the temperature for mixing and stirring the sodium hyaluronate aqueous solution and the strongly acidic cation exchange resin is 25-35° C., the stirring speed is 200-300 r / min, and the pH is 3-4 at the end of stirring.
[0016] Further preferably, the insoluble magnesium-containing compound is selected from one of magnesium hydroxide, magnesium carbonate and magnesium oxide, and the molar ratio of the insoluble magnesium-containing compound to the disaccharide unit of sodium hyaluronate is 0.5:1 to 2:1.
[0017] Further preferably, the reaction temperature after adding the insoluble magnesium-containing compound to the filtrate is 25-35° C., the stirring speed is 200-300 r / min, and the pH is 7-9 at the end of the reaction.
[0018] In the present invention, the strong acid cation exchange resin is added in excess. After a single reaction is completed, the sodium hyaluronate aqueous solution can be added multiple times for reaction until the pH change degree after the addition of the sodium hyaluronate aqueous solution is different from that of the previous reaction, and then the strong acid cation exchange resin is added again, thereby realizing semi-continuous production. The unreacted insoluble magnesium-containing compound filtered out by the present invention can be reused.
[0019] A nanoemulsion containing the anti-inflammatory composition.
[0020] The preparation method of the nanoemulsion comprises the following steps: After dissolving bisabolol in an oil phase solvent, a surfactant and 1,2-propylene glycol are added, and the mixture is stirred evenly. Under stirring conditions, a magnesium hyaluronate solution is added to obtain a nano primary emulsion of an O / W system, and then the nano emulsion is obtained by high pressure homogenization.
[0021] Preferably according to the present invention, the components in the nanoemulsion are calculated by mass as follows: 10-12 parts of bisabolol, 80-100 parts of oil phase solvent, 150-200 parts of surfactant, 150-200 parts of 1,2-propylene glycol, 10-15 parts of magnesium hyaluronate, and 570-620 parts of water.
[0022] Preferably according to the present invention, the oil phase solvent is selected from one or more of triacetin, isopropyl myristate, caprylic / capric triglyceride.
[0023] Preferably according to the present invention, the surfactant is selected from one or more of Tween 80, castor oil polyoxyethylene ether (EL-40), hydrogenated castor oil (CO-40), and polyoxyethylene hydrogenated castor oil (RH-40).
[0024] Application of the anti-inflammatory composition or the nanoemulsion in preparing products with anti-inflammatory effects.
[0025] Preferably according to the present invention, the product is a cosmetic or a skin care product.
[0026] Beneficial effects: 1. The present invention provides a composition with anti-inflammatory effect, which is mainly composed of magnesium hyaluronate and bisabolol. The present invention is based on the composition to prepare a nanoemulsion containing the anti-inflammatory composition, thereby improving the water solubility and permeability of bisabolol and enhancing the anti-inflammatory activity of the composition.
[0027] 2. The preparation method of magnesium hyaluronate of the present invention is simple, avoids the use of organic solvents, reduces sensitization, generates no waste, is environmentally friendly, and reduces industrial production costs, which is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are pictures of the morphology of the ammonium acryloyldimethyltaurate / VP copolymer solution and the solution after adding sodium / magnesium hyaluronate and inverting it.
[0029] Figure 2 It is a bar graph of NO release in the supernatant of RAW264.7 mouse macrophages.
[0030] Figure 3 It is a bar graph of IL-6 secretion in the supernatant of RAW264.7 mouse macrophages.
[0031] Figure 4 It is a bar graph of TNF-α secretion in the supernatant of RAW264.7 mouse macrophages. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below in conjunction with examples. It should be understood that the examples are only used to further illustrate and explain the present invention, and do not limit the protection scope of the present invention.
[0033] In the following examples, the sodium hyaluronate raw materials used were all from Shandong Baifu Freda Pharmaceutical Co., Ltd.; the strong acid styrene-based cation exchange resin used was from Shanghai Aladdin Biochemical Technology Co., Ltd., and the cross-linking degree was 7%.
[0034] In the following examples, the uronic acid content was detected by sulfuric acid-carbazole colorimetry, and the magnesium content and sodium content were detected by inductively coupled plasma emission spectrometry.
[0035] Example 1: Preparation of magnesium hyaluronate 400 g of sodium hyaluronate with a molecular weight of 380 kDa was weighed and stirred at a stirring speed of 200 r / min at room temperature until it was completely dissolved in 20 L of deionized water to obtain a sodium hyaluronate aqueous solution. Then, the sodium hyaluronate aqueous solution was added to a reaction vessel in which a sufficient amount of strong acid styrene cation exchange resin was previously placed, and stirred at a stirring speed of 200 r / min at 25°C. During the process, the pH was continuously detected, and the pH dropped from 7 to 3. After the stirring was completed, the hyaluronic acid filtrate was filtered and collected, and the hyaluronic acid filtrate was placed in a reactor, and 58.17 g of magnesium hydroxide was added to the reactor, and the reaction was carried out at 25°C at a stirring speed of 200 r / min. During the reaction, the pH was continuously detected, and the pH rose from 3 to 9. After the reaction was completed, the unreacted magnesium hydroxide was filtered to remove, and the filtrate was filtered through a 0.45µm filter membrane to obtain a hyaluronic acid magnesium solution, which was freeze-dried to obtain magnesium hyaluronate.
[0036] After testing, the uronic acid content in the magnesium hyaluronate product was 47.9%, the magnesium content was 2.72%, and the sodium content was 0.03%.
[0037] Example 2: Preparation of magnesium hyaluronate Weigh 400 g of sodium hyaluronate with a molecular weight of 15 kDa, stir at a stirring speed of 200 r / min at room temperature until it is completely dissolved in 10 L of deionized water to obtain a sodium hyaluronate aqueous solution. Then add the sodium hyaluronate aqueous solution to a reaction vessel pre-placed with a sufficient amount of strong acid styrene cation exchange resin, stir at a stirring speed of 200 r / min at 25°C, continuously detect the pH during the process, the pH drops from 7 to 3, and after stirring, filter and collect the hyaluronic acid filtrate, put the hyaluronic acid filtrate into a reactor, add 126.16 g of magnesium carbonate to the reactor, react at a stirring speed of 250 r / min at 30°C, continuously detect the pH during the reaction, the pH rises from 3 to 8, and after the reaction, filter and remove the unreacted magnesium carbonate, filter the filtrate through a 0.45µm filter membrane to obtain a magnesium hyaluronate solution, and freeze-dry to obtain magnesium hyaluronate.
[0038] After testing, the uronic acid content in the magnesium hyaluronate product was 46.7%, the magnesium content was 2.66%, and the sodium content was 0.03%.
[0039] Example 3: Preparation of magnesium hyaluronate 400 g of sodium hyaluronate with a molecular weight of 2000 kDa was weighed and stirred at a stirring speed of 300 r / min at room temperature until it was completely dissolved in 100 L of deionized water to obtain a sodium hyaluronate aqueous solution. Then, the sodium hyaluronate aqueous solution was added to a reaction vessel in which a sufficient amount of strong acid styrene cation exchange resin was previously placed, and stirred at a stirring speed of 300 r / min at 35°C. During the process, the pH was continuously detected, and the pH dropped from 7 to 3. After the stirring was completed, the hyaluronic acid filtrate was filtered and collected, and the hyaluronic acid filtrate was placed in a reactor, and 80.40 g of magnesium oxide was added to the reactor, and the reaction was carried out at 35°C at a stirring speed of 300 r / min. During the reaction, the pH was continuously detected, and the pH rose from 3 to 7. After the reaction was completed, the unreacted magnesium oxide was filtered to remove, and the filtrate was filtered through a 0.45µm filter membrane to obtain a magnesium hyaluronate solution, which was freeze-dried to obtain magnesium hyaluronate.
[0040] After testing, the uronic acid content in the magnesium hyaluronate product was 47.02%, the magnesium content was 2.62%, and the sodium content was 0.04%.
[0041] Example 4: Magnesium hyaluronate and bisabolol nanoemulsion After dissolving 1 g of bisabolol in 8 mL of triacetin, a mixed solution consisting of 15 g of Tween-80 and 15 g of 1,2-propylene glycol was added, and the mixture was thoroughly stirred. Then, 60 mL of a 2% by mass hyaluronate magnesium solution was slowly added under stirring, wherein the hyaluronate magnesium was prepared as in Example 1, to obtain an O / W system nano primary emulsion of hyaluronate and bisabolol, which was then homogenized at 60 MPa to obtain a nanoemulsion.
[0042] Example 5: Magnesium hyaluronate and bisabolol nanoemulsion After dissolving 1 g of bisabolol in 8 mL of isopropyl myristate, a mixed solution consisting of 20 g of EL-40 and 20 g of 1,2-propylene glycol was added and stirred evenly. Then, 60 mL of a 2% by mass hyaluronate magnesium solution was slowly added under stirring, wherein the magnesium hyaluronate was prepared as in Example 2, to obtain an O / W system nano primary emulsion of magnesium hyaluronate and bisabolol, which was then homogenized at 60 MPa to obtain a nanoemulsion.
[0043] Experimental Example 1: Permeability Test of Magnesium Hyaluronate The magnesium hyaluronate sample comes from Example 2, and the selected sodium hyaluronate sample has the same molecular weight as the magnesium hyaluronate; the magnesium hyaluronate and bisabolol nanoemulsion comes from Example 5; sodium hyaluronate having the same molecular weight as the magnesium hyaluronate in Example 2 is selected and the sodium hyaluronate and bisabolol nanoemulsion is prepared according to the method of Example 5.
[0044] Test method: According to GB-T27818-2011 "In vitro test method for skin absorption of chemicals", the permeation behavior of samples was studied at 2h, 4h, 8h, 12h and 24h based on the suckling pig skin-Franz cell system. The results are shown in Tables 1 and 2.
[0045] Table 1. The penetration of sodium hyaluronate and magnesium hyaluronate at different times (unit: μg / cm 2 )
[0046] As shown in Table 1, under the same conditions, the permeability of magnesium hyaluronate is higher than that of sodium hyaluronate. This may be because magnesium ions have weaker metallic properties than sodium ions and are more easily bound by negative charges, neutralizing the negative charge of hyaluronic acid. As a result, the main chain of hyaluronic acid cannot be fully stretched due to electrostatic repulsion, reducing its volume and improving permeability.
[0047] Table 2. The penetration of bisabolol at different times (unit: μg / cm 2 )
[0048] As shown in Table 2, under the same conditions, the permeability of bisabolol in the magnesium hyaluronate and bisabolol nanoemulsion is higher than that in the sodium hyaluronate and bisabolol nanoemulsion, which may be because magnesium ions are more easily bound by negative charges, and the emulsion formed under the same conditions is more stable. Therefore, the O / W nanoemulsion prepared from magnesium hyaluronate and bisabolol not only improves the water solubility of bisabolol, but also improves the permeability of bisabolol.
[0049] Experimental Example 2: Effect of Magnesium Hyaluronate on Cosmetic Thickeners Test method: The magnesium hyaluronate sample is from Example 1, and a 1% mass fraction of magnesium hyaluronate solution is prepared. Sodium hyaluronate with the same molecular weight as the above magnesium hyaluronate is selected to prepare a 1% mass fraction of sodium hyaluronate solution. The conductivity of the sodium hyaluronate solution and the magnesium hyaluronate solution are measured. The results are shown in Table 3.
[0050] Table 3. Conductivity of 1% mass fraction sodium hyaluronate solution and magnesium hyaluronate solution sample Conductivity Sodium hyaluronate solution 1364 μs / cm Magnesium Hyaluronate Solution 754.6 μs / cm The above results indicate that the conductivity of magnesium hyaluronate solution is lower than that of sodium hyaluronate solution, which may be because magnesium ions are easily bound by negative charges, resulting in a lower conductivity of magnesium hyaluronate than that of sodium hyaluronate.
[0051] Test method: Add 1% mass fraction of sodium hyaluronate and 1% mass fraction of magnesium hyaluronate solution to 0.6% mass fraction of ammonium acryloyldimethyltaurate / VP copolymer (AristoflexAVC) solution, respectively, until the final concentration of sodium hyaluronate and magnesium hyaluronate is 0.15% mass fraction, mix well, invert for 30 seconds, and observe its changes. The results are as follows: Figure 1 shown.
[0052] As can be seen from the figure, magnesium hyaluronate has less effect on the thickener AVC. After inversion for 30 seconds, the gel-like AVC sample did not show obvious flow phenomenon. Therefore, compared with sodium hyaluronate, magnesium hyaluronate is more conducive to improving the stability of thickeners in cosmetics.
[0053] Experimental Example 3: Protective effect of magnesium hyaluronate on ultraviolet-induced cellular oxidative damage The magnesium hyaluronate sample was from Example 1, the magnesium hyaluronate and bisabolol nanoemulsion was from Example 4, sodium hyaluronate with the same molecular weight as the magnesium hyaluronate in Example 1 was selected and the sodium hyaluronate and bisabolol nanoemulsion was prepared according to the method of Example 4, and human dermal fibroblasts (HDF-a cells) and human immortalized keratinocytes (HaCaT cells) were purchased from Guangzhou Jinio Biotechnology Co., Ltd.
[0054] Test method: HDF-a cells and HaCaT cells were cultured until the cell coverage was about 80-90% of the total area, and 90 mJ / cm 2 The cells were irradiated with UVB of the radiation intensity, and non-irradiated cells were set at the same time. After the irradiation, the experimental group 1 was added with a DMEM medium solution containing 0.05% mass fraction of magnesium hyaluronate, the experimental group 2 was added with a DMEM medium solution containing 0.05% mass fraction of sodium hyaluronate, the experimental group 3 was added with a DMEM medium solution containing magnesium hyaluronate and bisabolol nanoemulsion, wherein the total final concentration of magnesium hyaluronate and bisabolol was 0.05% mass fraction, the experimental group 4 was added with a DMEM medium solution containing sodium hyaluronate and bisabolol nanoemulsion, wherein the total final concentration of sodium hyaluronate and bisabolol was 0.05% mass fraction, and the control group was added with an equal amount of DMEM medium solution as the experimental group, and continued to culture for 24 h, and the proliferation rates of the two cells were measured. The results are shown in Tables 4 and 5.
[0055] Table 4. Proliferation rate of human dermal fibroblasts (HDF-a cells)
[0056] Table 5. Proliferation rate of human immortalized keratinocytes (HaCaT cells)
[0057] Analyzing the above results, after irradiation, the proliferation rates of HDF-a cells and HaCaT cells in the control group decreased to 27.47% and 33.95%, respectively, indicating that the UV-induced cell oxidative damage model was successfully constructed, while in experimental group 1, after irradiation, magnesium hyaluronate was added, and the proliferation rates of HDF-a cells and HaCaT cells increased to 49.77% and 55.26%, respectively, which was higher than that of sodium hyaluronate (experimental group 2), indicating that magnesium hyaluronate can resist UV-induced cell oxidative damage and promote cell proliferation. After preparing nanoemulsions with magnesium hyaluronate and sodium hyaluronate and bisabolol, the proliferation rates of HDF-a cells increased to 54.26% and 50.33%, respectively, and the proliferation rates of HaCaT cells increased to 60.12% and 56.62%, respectively, indicating that magnesium hyaluronate and sodium hyaluronate can play a synergistic role with bisabolol to repair cell oxidative damage together.
[0058] Experimental Example 4: In vitro anti-inflammatory activity of nanoemulsion of magnesium hyaluronate and bisabolol The magnesium hyaluronate sample was from Example 1; the magnesium hyaluronate and bisabolol nanoemulsion was from Example 4; sodium hyaluronate having the same molecular weight as the magnesium hyaluronate in Example 1 was selected and the sodium hyaluronate and bisabolol nanoemulsion was prepared according to the method of Example 4; 60 mL of magnesium hyaluronate solution was replaced with 60 mL of water and a bisabolol nanoemulsion not containing magnesium hyaluronate was prepared according to the method of Example 4; RAW264.7 mouse macrophages were purchased from Jin Shaoyuan (Shanghai) Biotechnology Co., Ltd.
[0059] Test method: LPS (lipopolysaccharide) was used to stimulate RAW264.7 mouse macrophages to produce an inflammatory response, and an experimental model was established. A blank group without LPS induction was also set up. After successful induction, the old culture medium was discarded, and a DMEM culture medium solution containing 0.05% mass fraction of hyaluronic acid magnesium was added to experimental group 1, and a DMEM culture medium solution containing bisabolol nanoemulsion was added to experimental group 2, in which the final concentration of bisabolol was 0.05% mass fraction. Experimental group 3 added a DMEM culture medium solution containing a mixture of bisabolol nanoemulsion and hyaluronic acid magnesium, in which the final concentration of hyaluronic acid magnesium was 0.023% mass fraction, and the final concentration of bisabolol was 0.027% mass fraction. Experimental group 4 added a DMEM culture medium solution containing a mixture of bisabolol nanoemulsion and hyaluronic acid magnesium, in which the final concentration of hyaluronic acid magnesium was 0.023% mass fraction, and the final concentration of bisabolol was 0.027% mass fraction. The DMEM medium solution of magnesium hyaluronate and bisabolol nanoemulsion, wherein the total final concentration of magnesium hyaluronate and bisabolol was 0.05% by mass, the experimental group 5 was added with the DMEM medium solution containing 0.05% by mass of sodium hyaluronate, the experimental group 6 was added with the DMEM medium solution containing sodium hyaluronate and bisabolol nanoemulsion, wherein the total final concentration of sodium hyaluronate and bisabolol was 0.05% by mass, the control group and the blank group were added with the same amount of DMEM medium solution as that of each experimental group, and the culture was continued for 24 h, and the amount of NO, IL-6 and TNF-α in the supernatant was detected. The results are as follows Figure 2 , Figure 3 , Figure 4 shown.
[0060] Under the same conditions, the inhibitory effects of sodium hyaluronate, magnesium hyaluronate and bisabolol on the release of NO, secretion of IL-6 and TNF-α of RAW264.7 mouse macrophages induced by LPS were not as good as those of magnesium hyaluronate and bisabolol nanoemulsion. Specifically, the release of NO, the secretion of IL-6 and TNF-α in experimental group 4 (hyaluronate magnesium and bisabolol nanoemulsion experimental group) were lower than those in experimental group 1 (hyaluronate magnesium experimental group) and experimental group 2 (bisabolol experimental group), and were also lower than those in experimental group 3 (hyaluronate magnesium and bisabolol mixed experimental group), indicating that the anti-inflammatory activity of the O / W nanoemulsion prepared by hyaluronate magnesium and bisabolol was enhanced, and hyaluronate magnesium and bisabolol showed a synergistic effect; in addition, the release of NO, the secretion of IL-6 and TNF-α in experimental group 4 (hyaluronate magnesium and bisabolol nanoemulsion experimental group) were also lower than those in experimental group 6 (sodium hyaluronate and bisabolol nanoemulsion experimental group), indicating that the nanoemulsion prepared by hyaluronate magnesium and bisabolol had stronger anti-inflammatory activity than sodium hyaluronate. The above results show that the nanoemulsion formed by hyaluronate magnesium and bisabolol has excellent anti-inflammatory activity and can be used to prepare cosmetics or skin care products with anti-inflammatory effects.
Claims
1. An anti-inflammatory composition, characterized in that Contains the following ingredients: Magnesium hyaluronate, bisabolol.
2. The anti-inflammatory composition according to claim 1, characterized in that The components of the anti-inflammatory composition are as follows, by mass: 10 to 15 parts of magnesium hyaluronate and 10 to 12 parts of bisabolol.
3. The anti-inflammatory composition according to claim 1, characterized in that The preparation method of magnesium hyaluronate is as follows: mixing a sodium hyaluronate aqueous solution with a strongly acidic cation exchange resin, filtering and collecting the filtrate after the stirring is completed, adding an insoluble magnesium-containing compound to the filtrate, filtering and removing the unreacted insoluble magnesium-containing compound after the reaction is completed, and freeze-drying the filtrate to obtain magnesium hyaluronate.
4. The anti-inflammatory composition according to claim 3, characterized in that Meet one or more of the following conditions: i. The molecular weight of the sodium hyaluronate is 3 kDa~3000 kDa, and the concentration of the sodium hyaluronate aqueous solution is 0.1~10%, mass percentage; ii. The strongly acidic cation exchange resin is a strongly acidic styrene cation exchange resin having a crosslinking degree of 5 to 10%; iii. The sodium hyaluronate aqueous solution and the strongly acidic cation exchange resin are mixed and stirred at a temperature of 25 to 35°C, a stirring speed of 200 to 300 r / min, and a pH of 3 to 4 at the end of stirring; iv. The insoluble magnesium-containing compound is selected from one of magnesium hydroxide, magnesium carbonate and magnesium oxide, and the molar ratio of the insoluble magnesium-containing compound to the sodium hyaluronate disaccharide unit is 0.5:1~2:1; v. After adding the insoluble magnesium-containing compound to the filtrate, the reaction temperature is 25-35°C, the stirring speed is 200-300 r / min, and the pH is 7-9 at the end of the reaction.
5. A nanoemulsion containing the anti-inflammatory composition of claim 1.
6. The method for preparing the nanoemulsion according to claim 5, characterized in that: The steps include: After dissolving bisabolol in an oil phase solvent, a surfactant and 1,2-propylene glycol are added, and the mixture is stirred evenly. Under stirring conditions, a magnesium hyaluronate solution is added to obtain a nano primary emulsion of an O / W system, and then the nano emulsion is obtained by high pressure homogenization.
7. The preparation method according to claim 6, characterized in that: The components in the nanoemulsion are calculated by weight as follows: 10-12 parts of bisabolol, 80-100 parts of oil phase solvent, 150-200 parts of surfactant, 150-200 parts of 1,2-propylene glycol, 10-15 parts of magnesium hyaluronate, and 570-620 parts of water.
8. The preparation method according to claim 6, characterized in that: The oil phase solvent is selected from one or more of triacetin, isopropyl myristate, and caprylic / capric triglyceride.
9. The preparation method according to claim 6, characterized in that: The surfactant is selected from one or more of Tween 80, castor oil polyoxyethylene ether, hydrogenated castor oil, and polyoxyethylene hydrogenated castor oil.
10. Use of the anti-inflammatory composition according to claim 1 or the nanoemulsion according to claim 5 in preparing a product with anti-inflammatory effect; Preferably, the product is a cosmetic or a skin care product.
Citation Information
Patent Citations
Magnesium hyaluronate for treating osteoarthritis and preparation method and application thereof
CN107840897A